HUKUM PIDANA ISLAM: PERSPEKTIF KEADILAN - Budianto, Kun (Nurani, 2013)
Abstract: In social life required a legal system to create aharmonious society and regularly so that justice can beachieved. The legal system is very diverse, and that diversity inthe legal system there are some that stand out. Western legalsystems are represented by two systems, namely the civil lawand common law, the legal system has been proved as the mostwidely adopted by many countries in the world. Another is thelegal system of Islamic law.ملخص:في الحیاة الاجتماعیة یتطلب نظاما قانونیا لخلق مجتمع متناغم وبشكل منتظمبحیث یمكن تحقیق العدالة .ولذلك، وبطبیعة الحال سوف تحدید النظام القانوني وفقالظروفھا .النظام القانوني ھي متنوعة جدا، وھذا التنوع في النظام القانوني ھناك بعضالتي تبرز .یتم تمثیل النظم القانونیة الغربیة عن طریق النظامین، وھما القانون المدنيوالقانون العام، وقد ثبت النظام القانوني باعتبارھا الأكثر، والتراسل الذي اتخذه العدیدمن البلدان في العالم .آخر ھو النظام القانوني للشریعة الإسلامیة .كل من النظامالقانوني ھو مركز الاھتمام في قلوب الفقھاء.Kata Kunci: hukum pidana islam, perubahan masyarakat